The Emerging Role of microRNAs in Aquaporin Regulation - Gomes, André; da Silva, Inês V.; Rodrigues, Cecília M. P.; Castro, Rui E.; Soveral, Graça (Frontiers in Chemistry, 2018)
Aquaporins (AQPs) are membrane channels widely distributed in human tissues. AQPs are essential for water and energy homeostasis being involved in a broad range of pathophysiological processes such as edema, brain injury, glaucoma, nephrogenic diabetes insipidus, salivary and lacrimal gland dysfunction, cancer, obesity and related metabolic complications. Compelling evidence indicates that AQPs are targets for therapeutic intervention with potential broad application. Nevertheless, efficient AQP modulators have been difficult to find due to either lack of selectivity and stability, or associated toxicity that hamper in vivo studies. MicroRNAs (miRNAs) are naturally occurring small non-coding RNAs that regulate post-transcriptional gene expression and are involved in several diseases. Recent identification of miRNAs as endogenous modulators of AQP expression provides an alternative approach to target these proteins and opens new perspectives for therapeutic applications. This mini-review compiles the current knowledge of miRNA interaction with AQPs highlighting miRNA potential for regulation of AQP-based disorders.